BICYCLE TRANSPORT AND MOBILITY MANAGEMENT IN RELATION TO ALTERNATIVE TRANSPORTATION TYPES (Perner's Contacts, 2011)
The article deals with cycling as one of the options of transportation services. This article also describes the management of mobility in relation to non-traditional means of transport.
Keywords: Bicycle transport; traffic safety; the Environment